Fostering the acquisition of subtraction strategies with interleaved practice: An intervention study with German third graders. (February 2021) - Nemeth, Lea; Werker, Katharina; Arend, Julia; Lipowsky, Frank
Abstract: Interleaved practice is a promising approach to foster the adaptive use of subtraction strategies. By intermixing strategies, comparison processes are evoked, which prompt more task-based strategy use. However, the effectiveness of interleaved practice in primary school mathematics has not been investigated yet. In the current study, 236 German third graders were randomly assigned to either an interleaved or a blocked condition. Both groups were instructed in using number-based strategies and the standard written algorithm for solving subtraction problems over 14 lessons. The students in the interleaved condition were prompted to compare strategies (between-comparison), while the students in the blocked condition compared the adaptivity of one strategy for different tasks (within-comparison). Our findings show that the students in the interleaved condition solved subtraction tasks with greater adaptiveness and accuracy. The effect on correctness was mediated by greater adaptive strategy use in the interleaved condition. Highlights: Interleaved practice can be successfully implemented in primary school classrooms. Interleaved practice fosters students' adaptive use of subtraction strategies. Moreover, it promotes students' accuracy in solving subtraction tasks. The benefit for students' correctness is mediated by gains in adaptivity. These benefits of interleaved practice are apparent in the short-term and long-term.